2007
DOI: 10.1111/j.1744-7909.2007.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐Wide Comparative Analysis and Expression Pattern of TCP Gene Families in Arabidopsis thaliana and Oryza sativa

Abstract: Several TCP genes have been reported to play important roles in plant development; the TCP homologs encode a plant-specific family of putative transcription factors. To understand the evolutionary relationship of TCP genes of Arabidopsis thaliana and Oryza sativa L. (hereafter called rice), we have identified 23 and 22 TCP genes in the Arabidopsis and rice genomes, respectively. Using phylogenetic analysis, we grouped these TCP genes into three classes. In addition, the motifs outside the TCP domain further su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
115
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(136 citation statements)
references
References 34 publications
20
115
0
1
Order By: Relevance
“…While no obvious devel-opmental defects were observed in the stamen and lemma of the rep1 mutants, this may be a reflection of functional redundancy of other genes with REP1 due to gene duplication events of TCP domain family members, or alternatively may mean that REP1 has no critical role in stamen and lemma development. Our phylogenetic analysis revealed 22 putative TCP domaincontaining members in the rice genome (Yao et al, 2007), supporting the hypothesis that lineage-specific expansions of the TCP family members happened during rice genome evolution (Navaud et al, 2007). Therefore, investigations on the REP1-like proteins in the relative grass family will help us to elucidate whether the conserved pathway exists in controlling other grass floral zygomorphy.…”
Section: Rep1 Is a Tcp Family Member With A Distinct Expression Patternmentioning
confidence: 60%
See 2 more Smart Citations
“…While no obvious devel-opmental defects were observed in the stamen and lemma of the rep1 mutants, this may be a reflection of functional redundancy of other genes with REP1 due to gene duplication events of TCP domain family members, or alternatively may mean that REP1 has no critical role in stamen and lemma development. Our phylogenetic analysis revealed 22 putative TCP domaincontaining members in the rice genome (Yao et al, 2007), supporting the hypothesis that lineage-specific expansions of the TCP family members happened during rice genome evolution (Navaud et al, 2007). Therefore, investigations on the REP1-like proteins in the relative grass family will help us to elucidate whether the conserved pathway exists in controlling other grass floral zygomorphy.…”
Section: Rep1 Is a Tcp Family Member With A Distinct Expression Patternmentioning
confidence: 60%
“…S4; Feng et al, 2006;Navaud et al, 2007;Yao et al, 2007). Therefore, functional analysis on REP1 Note that six genes were deleted in the rep1-1 mutant.…”
Section: Cloning and Annotation Of The Rep1 Genementioning
confidence: 99%
See 1 more Smart Citation
“…The two amphipathic helical regions are abundant in hydrophobic amino acid residues (Ala, Leu, and Trp), whereas the Loop region contains the hydrophilic amino acids residues (Gly), and all the conserved amino acid residues possibly contribute to the function of DNA binding, protein-protein interactions, and protein nuclear localization (Kosugi and Ohashi, 2002;Yao et al, 2007;Viola et al, 2011). Bioinformatics analysis indicated that the bHLH domain exists in all TCP proteins; only a few of the TCP proteins contain the R domain, which include polar residues and is assumed to develop a hydrophilic α-helix involved in protein-protein interactions (Yao et al, 2007). Based on the variation in the TCP domain, 61 NtTCP proteins can be classified into two groups, known as class I and class II.…”
Section: Introductionmentioning
confidence: 99%
“…TEOSINTE-BRANCHED1/CYCLOIDEA/PCF (TCPs) constitute a large group of plant-specific genes found in various species, ranging from lower to higher plants, with 24 TCPs in Arabidopsis (Arabidopsis thaliana) and more than 20 TCPs in rice (Oryza sativa; Cubas, 2002;Navaud et al, 2007;Yao et al, 2007). TCP proteins have a TCP domain that contains a helix-loop-helix (bHLH) motif (Martín-Trillo and Cubas, 2010).…”
mentioning
confidence: 99%